CFD Analysis of Centrifugal Pump with Impeller Made of Various Materials - Raut, Shrikant Vasant; Arakerimath, Dr. R. R. (Engineering And Technology Journal, 2022)
The purpose of this study is to model and simulate CFD in centrifugal pump with different impeller material. Using CFD technique impeller with four different materials are analysed and compared. Aluminium, steel ,T300 and glass fibre are the four materials are used for study. T300and glass fibbers are belong to composite fibre (additive manufacturing). From result, data is compared and performance of centrifugal pump with impeller made by additive materials are compared with steel and aluminium. Results shows that composite materials (T300 and Glass fibre give performance as same as steel , so composite material or additive manufacturing for impeller can replace conventional metals like steel and aluminium.